Pengaruh kepemimpinan kepala sekolah, motivasi berprestasi, dan kompensasi terhadap kedisiplinan guru SMP negeri se-Kabupaten Bantul - Windarti Windarti; Mundilarno Mundilarno (Universitas Sarjanawiyata Tamansiswa, 2016)
This study was aimed at revealing the effect of headmaster’s leadership, achievement motivation, and compensation on the teachers’ discipline of the Junior High School Teachers in Districts Bantul. The study was conducted in Junior High School Bantul sub-district Bantul Regency in academic year 0f 2013-2014. This research is a quantitative one using survey method. The population of this research is 105 teachers from 3 Junior High School on district Bantul, Special Province of Yogyakarta, and a sample of 105 teachers, was established using population sample. The descriptive analysis result shows that the principals’ leadership give positive impact and significant of teacher’s discipline. Achievement motivation gives positive impact and significant of teacher’s discipline, and compensation gives positive impact and significant for teacher’s discipline. And simultaneously principals’ leadership, achievement motivation, and compensation gives positive impact and is significant for junior high school teacher’s discipline in Bantul sub-district Bantul Regency. Effective contribution all together is 44.5%. Effective contribution individually of The headmaster’s leadership on the discipline teacher’s is 52.1%, The compensation on the discipline teacher’s is 28.3%, and the compensation on the discipline teacher’s is 19.5% of the junior high school in Bantul District, Bantul Regency, Special Province of Yogyakarta.